CYTOPROTECTION WITH TRIMETAZIDINE MB: RECENT DATA - I. G. Gordeev; E. E. Luchinkina; E. O. Taratukhin (Российский кардиологический журнал)
The article focuses on new data on trimetazidine MB cytoprotection studies. The data provided on novel mechanisms of its effect including systemic action not related to myocardium. The results of epidemiological studies and meta-analysis are provided that confirm safety and efficacy of the medication in ischemic heart disease and chronic heart failure.